Molecular and Electronic Structures, Spectra, Electrochemistry and Anti‐bacterial Efficacy of Novel Heterocyclic Hydrazones of Phenanthrenequinone and Their Nickel(II) Complexes. Issue 34 (9th September 2022) - Dinda, Soumitra; Maitra, Debapriya; Roy, Bedaprana; Khan, Prattusha; Samajdar, Aratrika; Mitra, Arup Kumar; Roy, Subhadip; Mondal, Arpan; Pramanik, Kausikisankar; Ganguly, Sanjib
Abstract: A pair of tridentate ligands incorporating heterocyclic hydrazones of 9, 10‐phenanthrenequinone viz, . pyridyl‐hydrazino‐phenathrenequinone HL Py 1a and benzothiazolyl‐hydrazino‐phenathrenequinone HL Benz 1b have been synthesized and both behave as monoanionic towards nickel(II), forming meridional octahedral complexes of type [Ni(L Py )2 ] 2a and [Ni(L Benz )2 ] 2b as evident from single crystal X‐ray diffraction studies. The complexes are electro‐active in solution and nature of redox orbitals has been analysed by theoretical means. They display two oxidative and two reductive responses that have been ascribed to the redox processes of coordinated ligands. The electronic absorption spectral patterns of two complexes are analogous barring the fact that lower energy transition for 2b is marginally bathochromically shifted relative to that of 2a and it has been clarified by TD‐DFT studies. Anti‐bacterial efficacy of the ligands HL Py 1a, HL Benz 1b and complexes [Ni(L Py )2 ] 2a, [Ni(L Benz )2 ] 2b against four Gram‐positive and four Gram‐negative strains has been explored. [Ni(L Py )2 ] 2a exhibits more pronounced efficacy than [Ni(L Benz )2 ] 2b and these are greater than those of the corresponding ligands. The mode of action of 2a is essential via DNA damage while protein leakage and membrane lipid damage were observed upon treatment with 2b . Abstract : The antimicrobial activity and biofilm forming ability of two new homoleptic nickel(II) complexes of 9, 10‐phenanthrenequinone grafted pyridyl and benzothiazolyl hydrazones have been explored along with in depth analysis of their electrochemical and spectral properties.